PELATIHAN MEDIA PEMBELAJARAN KURIKULUM MERDEKA UNTUK GURU SD DI DESA WIBAWAMULYA - Rosmiati, Anisah; Indah Muslimah, Alfiana; Rikmasari, Rima (An-Nizam, 2024)
The ability to utilize the latest technology is one of the important things in creating an effective and engaging learning experience. Technological changes require educators who are accustomed to using traditional learning media to become technology-based learning media. The independent curriculum learning media training for elementary school teachers in Wibawamulya Village aims to improve teachers' ability to design learning media that is effective and appropriate for the teaching and learning process. This program focuses on developing teachers' skills in using media that support more flexible, creative and fun learning. Through this training, teachers are expected to utilize various learning media that can increase student engagement and understanding. The methods used in this training include theory, hands-on practice, and case studies relevant to the local context. The results of this training are expected to support the achievement of the independent curriculum objectives and improve the quality of education in Wibawamulya Village.